STUDYING THE PROCESS OF PRODUCING SODIUM SILICATE AND FLUORIDE FROM Na2SiF6 BY HYDROLYSIS WITH SODIUM HYDROXIDE (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this paper, to return acid-soluble silicon dioxide to the initial stage of the process of defluoridation of EPA in the form of a sodium silicate solution, the solid phase that has passed through the stages of filtration and washing is hydrolyzed with a NaOH solution. The hydrolysis products of Na2SiF6 are NaF and CaF2. Results of studies on the influence of the norm on the degree of hydrolysis and the change in the L:S ratio, as well as on the chemical composition of the solid and liquid phases during the hydrolysis of Na2SiF6 with sodium hydroxide.